Partial Characterization of a Beta-Lactamase from Vibrio parahaemolyticus by a New Automated Microiodometric Technique - DeBell, Robert M. (1978)
A number of characteristics were determined with a new automated method for a partially purified β-lactamase from Vibrio parahaemolyticus. The enzyme had a molecular weight of 28,000 by gel filtration, a pH optimum between 6.5 and 7.0, and a temperature optimum at 36°C. With penicillin G as the substrate, the K(m) value for the β-lactamase was 54.4 μM. The β-lactamase was inhibited by cloxacillin but not by p-chloromercuribenzoate. The enzyme was similar but not identical to β-lactamases from gram-negative, “nonhalophilic” organisms described by other workers. The microiodometric assay to measure β-lactamase activity was automated with the use of a centrifugal analyzer that permitted 14 simultaneous determinations. Within-run precision was tested by putting the same reaction mixture in each well, and the coefficient of variation was only about 3%. Four extracts from different strains of halophilic vibrios were used to demonstrate that reaction rates were linear with enzyme concentration. The correlation coefficient of activity by the automated method with activity by the spectrophotometric method was 0.9721, demonstrating that the methods compared favorably with each other. The automated method greatly facilitated the characterization of the β-lactamase.